Kemampuan Berpikir Kreatif dan Hasil Belajar Matematika Siswa Menggunakan Model Pembelajaran Project-Based Learning Berbasis Pendekatan STEM - I Wayan Widana; Kadek Lisa Septiari (Jurnal Elemen, 2021)
Creative thinking is one of the competencies needed in the Industrial Revolution 4.0, where change is very dynamic, so it must be balanced with an irregular way of thinking. This study analyzes the effect of the project-based learning models on the STEM approach to creative thinking skills and mathematics learning outcomes. The population was grade VII students of SMP PGRI 6 Denpasar in the 2019/2020 school year. The sample of the experimental class and the control class used the random sampling technique. The experimental class was given treatment with a project-based learning model based on the STEM approach, while the control group used a conventional project-based learning model. Data on creative thinking skills were collected using a questionnaire, and data on mathematics learning outcomes were collected using essay tests. Data were analyzed using the Manova test. The results of the study: there is an effect of the STEM approach-based project-based learning model on creative thinking skills; there is an effect of project-based learning model based on STEM approach on mathematics learning outcomes; there is an effect of the project-based learning model based on the STEM approach together on creative thinking skills and mathematics learning outcomes.